"Purely Artistic": Police Power and Popular Culture in Colonial Algerian Theater. Issue 2 (1st June 2020) - Beaujon, Danielle
Abstract: Following World War II, French police surveillance in Algeria increasingly focused on the threat of Algerian nationalism and policing theater proved no exception. The police assiduously investigated the contents of plays and the background of performers, seeking to determine whether a performance could be considered "purely artistic." In cracking down on theater, the police attempted to produce "pro-French" art that could influence Algerian loyalties, a cultural civilizing mission carried out by the unlikely figure of the beat cop. Ultimately, their mission failed. Live performances presented an opportunity for spontaneity and improvisation that revealed the weakness of colonial policing. In this article, I argue that in trying to separate art from politics, the police created an impossibly capacious idea of the political, giving officers justification for inserting themselves into intimate moments of daily life. The personal, the interpersonal, and the artistic became a realm of police intervention.